Taḥlīlu al Istiṡnā’i bi Illā wa Ghairu fī Kitābi al Ażkāri li al Imāmi al Nawawī - Putra, Lidin Wiwah Jaya; Buska, Wahyudi (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
In this thesis the author discusses istisna 'with illa and ghairu. The aims of this research are to: know the kinds of istisna', determine the law of the word that lies after illa and ghairu, and understand the benefits of the istisna' sentence in the book of al-azdkar by Imam Nawawi. The type of research used is qualitative research. The source of research data is the book of al-Azdkar written by Imam Nawawi. The object of this research is various kinds of istisna', i'rab words that are located after illa and ghairu, and the benefits of the sentence istisna'. Data collection techniques used are reading and note-taking techniques. The instrument used is the author assisted by text data, writing instruments and a laptop. The method used to analyze the data is a description of the analysis. From the results of this study, the writer concludes that: the sentence that is istisna'kan with illa is 31 sentences, while the sentence that is istisna'kan with ghairu is 22 sentences. Each of these sentences is analyzed in various ways, the i'rab-i'rab words that are located after the custom, and the benefits of the istisna' sentence.